Propofol-based total intravenous anaesthesia is associated with better survival than desflurane anaesthesia in hepatectomy for hepatocellular carcinoma: a retrospective cohort study. (August 2019) - Lai, Hou-Chuan; Lee, Meei-Shyuan; Lin, Chin; Lin, Kuen-Tze; Huang, Yi-Hsuan; Wong, Chih-Shung; Chan, Shun-Ming; Wu, Zhi-Fu
Abstract: Background: Previous studies have shown that anaesthetic technique can affect outcomes of cancer surgery. We investigated the association between anaesthetic technique and patient outcomes after elective hepatectomy for hepatocellular carcinoma. Methods: This was a retrospective single-centre cohort study of patients who received elective hepatectomy for hepatocellular carcinoma from January 2005 to December 2014. Patients were grouped according to propofol or desflurane anaesthesia. Kaplan–Meier analysis was performed and survival curves were constructed from the date of surgery to death. After propensity matching, univariable and multivariable Cox regression models were used to compare hazard ratios for death. Subgroup analyses were performed for tumour–node–metastasis staging and distant metastasis and local recurrence. Results: A total of 492 patients (369 deaths, 75.0%) with desflurane anaesthesia and 452 (139 deaths, 30.8%) with propofol anaesthesia were eligible for analysis. After propensity matching, 335 patients remained in each group. In the matched analysis, propofol anaesthesia had a better survival with hazard ratio of 0.47 (95% confidence interval, 0.38–0.59; P <0.001). Subgroup analyses also showed significantly better survival in the absence of distant metastasis (hazard ratio, 0.47; 95% confidence interval, 0.37–0.60; P <0.001) or local recurrence (hazard ratio, 0.22; 95% confidence interval, 0.14–0.34; P <0.001) in the matched groups. Conclusions: Propofol anaesthesia was associated with better survival in hepatocellular carcinoma patients who underwent hepatectomy. Prospective studies are warranted to evaluate the effects of propofol anaesthesia on surgical outcomes in hepatocellular carcinoma patients.